ANALISIS STRATEGI E-CHANNEL PT. BANK RAKYAT INDONESIA DI REGIONAL OFFICE PADANG - Olin Nofita; Syafrizal; Fajri Adrianto (Halu Oleo University, 2024)
The aim of this research is to analyze the e-channels strategy of Bank BRI Regional Padang. Analysis was carried out using the business model canvas (BMC) and SWOT analysis. In this research, 3 informants were taken from within the company. The research stages begin with the Business Model Canvas and SWOT, problem identification, data collection, data analysis, interpretation of results and conclusions. Through the analysis described above, the results obtained show that Bank BRI has implemented the Business Model Canvas. Based on the results of the SWOT matrix, 14 alternative strategies were obtained that Bank BRI Regional Office Padang could choose in an effort to improve e-channel. After carrying out the SWOT analysis, further development was carried out by adding additions to each element of the 9 BMC blocks to produce a new business model canvas on the BRI Bank e-channel. The limitations of this research are limited to only using the Business Model Canvas analysis method and SWOT analysis. It is recommended to use the analysis method using QSPM to get better results. The informants in this research only focused on informants who came from within the company. It is recommended that further research include informants from external parties such as the OJK.